2006
DOI: 10.1055/s-2006-925362
|View full text |Cite
|
Sign up to set email alerts
|

Argon Plasma Ablation of Gastric Inlet Patches in the Cervical Esophagus may Alleviate Globus Sensation: A Pilot Trial

Abstract: Our preliminary data suggest that ablation of gastric inlet patches by APC can alleviate chronic globus sensation or sore throat. Acid reflux or its treatment is unlikely to influence these results. A randomized and blinded study is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 7 publications
1
40
0
4
Order By: Relevance
“…What about the effectiveness? Recent studies have demonstrated a convincing symptom relief derived from endoscopic ablation of CIP in the short term [10,19], but data is lacking regarding the long-term outcome. Here we aimed to evaluate the long-term efficiency of this treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…What about the effectiveness? Recent studies have demonstrated a convincing symptom relief derived from endoscopic ablation of CIP in the short term [10,19], but data is lacking regarding the long-term outcome. Here we aimed to evaluate the long-term efficiency of this treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In very few patients, in the literature only presented in form of case reports, complicated courses can develop out of CIP and may lead to a wide clinical spectrum ranging from ulcers, strictures, perforation, fistulas or at worst the development of adenocarcinomas in the esophagus [15,16,17,18]. In a feasibility study and a consecutive sham-controlled study we were able to show that an endoscopic ablation of inlet patches using argon plasma coagulation (APC) led to significant short-term symptom relief of globus sensation [10,19]. However, there are no data on long-term outcomes in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Complications of strictures and webs are amenable to standard esophageal dilation techniques, with the caveat that detection of such strictures can be more difficult given the location adjacent to the UES. Transendoscopic thermal ablation combined with high-dose omeprazole therapy and argon plasma ablation have been shown to allow replacement of the inlet patch by normal squamous mucosa, with resolution of related symptoms [126,127]. As most patients are asymptomatic and symptomatic patients should respond to acid inhibition or dilation, the role for ablation techniques is yet undefined.…”
Section: Heterotopic Gastric Mucosa (Inlet Patch)mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Few attempts have been made to treat these lesions. 18,19 A recent randomized controlled trial in adults with globus associated with GIP showed a significant improvement is symptoms after using argon plasma coagulation (APC) as compared to a sham operation. 20 APC has also been shown to be safe and effective for ablation of vascular lesions in children.…”
Section: Introductionmentioning
confidence: 99%